Karakterisasi 14 Genotipe Kacang Panjang (Vigna sinensis) di Dataran Rendah Bengkulu - Togatorop, Eny Rolenti; Novita Sari, Dia; Novita Sari, Dian; Susilo, Edi; Parwito (Jurnal Hortikultura Indonesia, 2020)
The production of long beans at Bengkulu province is still concentrated in highland regions. The possibilities for increasing long bean production in the lowlands of Bengkulu by create superior varieties to produce the high yielding varieties and well adapted to lowland ecosystems. It is important to classify the explored genotypes as preliminary knowledge for the production of parental genotype on long bean crossing. The research aimed to characterize 14 genotypes of long beans grown on the lowland Bengkulu. This research was conducted at the Kebun Percobaan Kelurahan Medan Baru, Kecamatan Muara Bangkahulu Bengkulu province with 10 m above the sea level (asl). The experiment design was used a complete randomized block with three replications. The result showed that the genotypes KPG4, KPG8, KPG12, KPG13, and KPG14 had early maturity, high pod length, weight per pod, and pod weight per plant and also had a green color and crunchy texture. Cluster analysis of 14 genotypes of long beans based on the quantitative character resulted in 5 groups and principal component analysis resulted in 3 main components with the cumulative diversity of 82.54%. Keywords: dendogram, coefficient of variance, exploration, pod length, germplasm, selection